Measurement of the pp → ZZ production cross section and constraints on anomalous triple gauge couplings in four-lepton final states at √s = 8 TeV - Khachatryan, V. (2015)
A measurement of the inclusive ZZ production cross section and constraints on anomalous triple gauge couplings in proton-proton collisions at root s = 8 TeV are presented. The analysis is based on a data sample, corresponding to an integrated luminosity of 19.6 fb(-1), collected with the CMS experiment at the LHC. The measurements are performed in the leptonic decay modes ZZ -> lll'l', where = e, mu and l'= e, mu, tau. The measured total cross section sigma(pp -> ZZ) = 7.7 +/- 0.5 (stat) (0)(-0.4)(+0.5) (syst) +/- 0.4 (theo) +/- 0.2 (lumi) pb, for both Z bosons produced in the mass range 60 < m(z) < 120 GeV, is consistent with standard model predictions. Differential cross sections are measured and well described by the theoretical predictions. The invariant mass distribution of the four-lepton system is used to set limits on anomalous ZZZ and ZZ gamma couplings at the 95% confidence level: -0.004 < f(4)(Z), < 0.004, -0.004 < f(5)(Z) < 0.004, -0.005 < f(5)(Z) < 0.005, and -0.005 < f(5)(Y) < 0.005. (C) 2014 The Authors. Published by Elsevier B.V.